2015
DOI: 10.1155/2015/784626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Self-Assembled Monolayers with Different Chemical Groups on Ovarian Cancer Cell Line BehaviorIn Vitro

Abstract: In addition to serving as a physical support, the extracellular matrix (ECM) actively influences cell behavior. However, the definitive effects of different chemical structures present in the ECM on cell behavior remain obscure. The current study aimed to investigate the effects of different chemical structures present in the ECM on cellular physiology using the ovarian cancer cell line SKOV-3 as a model. Self-assembled monolayers (SAMs) with different chemical modifications, including methyl (-CH3), hydroxyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The bare flat gold surface is slightly hydrophilic in nature, and the water contact angle was found to be 71 ± 4° very closely matching the literature value ~66–70° [60, 61], even though the flat gold was prepared using different techniques. Immobilization of hydrophobic C 12 -SH on the gold surface increases the contact angle from 71 ± 4° to 104 ± 2°, decreasing the wettability and this value is in accordance with the previously reported values 103 ± 3° [62] and 110° [63]. These very closely matching contact angles of bare flat gold and SAMs of C 12 -SH with the literature values helps us verify the sensitivity of our simple home-made setup.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The bare flat gold surface is slightly hydrophilic in nature, and the water contact angle was found to be 71 ± 4° very closely matching the literature value ~66–70° [60, 61], even though the flat gold was prepared using different techniques. Immobilization of hydrophobic C 12 -SH on the gold surface increases the contact angle from 71 ± 4° to 104 ± 2°, decreasing the wettability and this value is in accordance with the previously reported values 103 ± 3° [62] and 110° [63]. These very closely matching contact angles of bare flat gold and SAMs of C 12 -SH with the literature values helps us verify the sensitivity of our simple home-made setup.…”
Section: Resultssupporting
confidence: 91%
“…For galactose SAMs with a slightly different linker than ours, total wetting has been observed [65]. The carboxyl-terminated alkanethiol shows a contact angle of 39 ± 3° which is slightly lower than the reported value 50 ± 2° [62]. Finally, the contact angle of HO-PEG 2 -SH SAMs has been determined to be 64± 3°.…”
Section: Resultsmentioning
confidence: 60%
“…can be employed for the surface activation of nanofibrous TE scaffolds. Different authors have already focused on examining the impact of a nitrogen (N 2 ) plasma on the surface characteristics and cellular interactions of electrospun scaffolds [180,[252][253][254][255]. In 2014, Dolci et al [252] employed a linear corona discharge sustained in N 2 at atmospheric pressure to modify the surface properties of electrospun PLLA scaffolds [256].…”
Section: Plasma Activationmentioning
confidence: 99%
“…As different studies have observed superior cell growth on NH 2 -enriched surfaces in comparison to other functionalized surfaces [255,257], efforts have also been undertaken to specifically graft NH 2 functional groups using NTPs on nanofibrous TE scaffolds. For this purpose, plasmas sustained in ammonia (NH 3 ) have been commonly applied, although also in this case only a small percentage of nitrogen is generally incorporated as NH 2 groups.…”
Section: Plasma Activationmentioning
confidence: 99%
“…Other chemical groups than the carboxylic group can also be studied to support the PSC maintenance because the cell behaviors (not PSCs) mainly the cell spreading have been shown to significantly change by the substrates with different chemical groups, like amine, carboxylic, hydroxyl, methyl or mercaptol [129][130][131][132][133]. An important message is that the limited spreading of PSCs induced by the tailored simple surface chemistry is indicative of the self-renewal ability.…”
Section: Chemical Groupsmentioning
confidence: 99%